Evaluating the Impact of the Department of Defense Regional Centers for Security Studies - Hanauer, Larry (RAND Corporation, 2014)
The five U.S. Department of Defense (DoD) Regional Centers for Security Studies have been helping partner nations build strategic capacity for almost 20 years. They are high-impact components of U.S. security cooperation and engagement efforts, despite their relatively small budgets. This study analyzes the centers' contributions to DoD policy priorities and the ways in which they assess their programs.